Language Dominance in Patients With Malformations of Cortical Development and Epilepsy - Kuchukhidze, Giorgi; Siedentopf, Christian; Unterberger, Iris; Koppelstaetter, Florian; Kronbichler, Martin; Zamarian, Laura; Haberlandt, Edda; Ischebeck, Anja; Delazer, Margarete; Felber, Stephan; Trinka, Eugen (Frontiers in Neurology, 2019)
Background: Language function may be reorganized in patients with malformations of cortical development (MCD). This prospective cohort study aimed in assessing language dominance in a large group of patients with MCD and epilepsy using functional MRI (fMRI). Methods: Sixty-eight patients (40 women) aged 10–73 years (median, 28.0; interquartile range, 19) with MCD and epilepsy underwent 1.5 T MRI and fMRI (word generation task). Single-subject image analysis was performed with statistical parametric mapping (SPM12). Language lateralization indices (LIs) were defined for statistically significantly activated voxels in Broca's and Wernicke's areas using the formula: LI = (VL – VR)/(VL + VR) × 100, where VL and VR were sets of activated voxels on the left and on the right, respectively. Language laterality was considered typical if LI was between +20 and +100 or atypical if LI was between +19 and −100. Results: fMRI signal was elicited in 55 of 68 (81%) patients. In 18 of 55 (33%) patients, language dominance was typical, and in 37 of 55 (67%) patients, atypical (in 68%, right hemispheric; in 32%, bilateral). Language dominance was not influenced by handedness, electroclinical, and imaging features. Conclusions: In this prospective study on a large group of patients with MCD and epilepsy, about two-thirds had atypical language dominance. These results may contribute to assessing risks of postsurgical language deficits and could assist in planning of “cortical mapping” with intracranial electrodes in patients who undergo presurgical assessment.